2019
DOI: 10.1055/s-0039-1678675
|View full text |Cite
|
Sign up to set email alerts
|

Higher Axial Tibiofemoral Rotation and Functional Outcomes with Mobile-Bearing Compared with Fixed-Bearing Total Knee Arthroplasty at 1- but Not at 2-Year Follow-Up—A Randomized Clinical Trial

Abstract: The objective of this study was to determine in vivo knee kinematics and clinical outcomes of patients who underwent fixed- and mobile-bearing total knee arthroplasty (TKA) at 1- and 2-year follow-up. This prospective double-blinded randomized controlled trial was performed from November 2011 to December 2012. A total of 64 patients were randomized to fixed- and mobile-bearing TKA groups (32 patients in each group). All patients were evaluated with the following: three-dimensional in vivo knee kinematics analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…'s study concluded that MB TKA allowed a higher degree of axial tibiofemoral rotation when walking, stepping up stair steps, and standing up from a chair and had higher functional outcomes compared with FB TKA at 1-year follow-up by knee kinematics analysis. But, they did not compare with the healthy group [34]. Zürcher et al.…”
Section: Discussionmentioning
confidence: 99%
“…'s study concluded that MB TKA allowed a higher degree of axial tibiofemoral rotation when walking, stepping up stair steps, and standing up from a chair and had higher functional outcomes compared with FB TKA at 1-year follow-up by knee kinematics analysis. But, they did not compare with the healthy group [34]. Zürcher et al.…”
Section: Discussionmentioning
confidence: 99%
“…The minimal functional improvement may be explained by greater axial rotation promoted by the MB implants [ 29 , 53 , 99 ]. Amaro et al [ 8 ] evaluating kinematic differences in 64 patients, found that axial rotation was higher in the MB group after 1 year, but disappeared at 2-year follow-up. A histological study showed the development of fibrotic tissue in the synovial membrane and infrapatellar fat pad after a TKA [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…A histological study showed the development of fibrotic tissue in the synovial membrane and infrapatellar fat pad after a TKA [3]. This produces a hardening effect that may minimize the kinematic differences between the MB and FB groups [8] The rate of deep infection was strongly influenced by the study by Breeman et al [17], which weighted 17.6% on the final effect. Indeed, when conducting the analyses without those data [17], the rate of deep infection is similar between the two groups.…”
Section: Kim Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…of motion (ROM) of the knee joint, 10 and provide better functional outcomes. 11 Meanwhile, several disadvantages of MB-TKA were described, such as dislocation of the insert, an increased risk of soft tissue impingement, and a prolonged learning curve. 12,13 Although MB-TKA has some theoretical advantages compared with FB-TKA, controversy still remains which type of prosthesis provides better clinical and radiographic outcomes in long-term follow-up.…”
mentioning
confidence: 99%